Constitutive expression of the granulocyte-macrophage colony-stimulating factor gene in acute myeloblastic leukemia. - Young, D C (1987)
Expression of the granulocyte-macrophage colony-stimulating factor (GM-CSF) gene was studied by Northern blot analysis in normal human hematopoietic cells and a series of leukemias. GM-CSF messenger (m)RNA was detected in activated T cells, but not in normal bone marrow cells, monocytes, or nonactivated T cells. In contrast, leukemic cells from 11 of 22 cases of acute myeloblastic leukemia expressed GM-CSF transcripts. Biologically active CSF was detected in supernatant conditioned by 6 of these 11 leukemias. Expression of the GM-CSF gene was not detected in "common" (pre-B cell) acute lymphoblastic leukemia (11 cases tested) or chronic myeloid leukemia (4 cases tested). These results show that the GM-CSF gene is constitutively expressed in a subset of patients with AML, and further suggest that expression of this gene could contribute to the abnormal growth properties characteristic of AML.